2010
DOI: 10.1111/j.1476-5381.2009.00547.x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing QT liability and proarrhythmic risk in drug discovery and development

Abstract: Drug-induced torsades de pointes (TdP), a rare, life-threatening, polymorphic, ventricular tachycardia associated with prolongation of the QT interval, has been the main safety reason for the withdrawal of medicines from clinical use over the last decade. Most often, drugs that prolong the action potential and delay ventricular repolarization do so through blockade of outward (repolarizing) currents, predominantly the rapid delayed rectifying potassium current, IKr. While QT interval prolongation is not a safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…Torsades de Pointes is a rare, polymorphic, ventricular tachycardia associated with the prolongation of the QT interval [1]. Specifically, there is strong evidence that the prolongation effects of drug candidates on the QT interval form a risk factor for TdP and sudden cardiac death [2,3]. In view of this, the prolongation of the QT interval represented the reason for about one-third of drug withdrawals between 1990 and 2006, as reported in [4][5][6], involving different therapeutic areas [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Torsades de Pointes is a rare, polymorphic, ventricular tachycardia associated with the prolongation of the QT interval [1]. Specifically, there is strong evidence that the prolongation effects of drug candidates on the QT interval form a risk factor for TdP and sudden cardiac death [2,3]. In view of this, the prolongation of the QT interval represented the reason for about one-third of drug withdrawals between 1990 and 2006, as reported in [4][5][6], involving different therapeutic areas [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…International Conference on Harmonization (ICH) S7A, S7B and E14 [12][13][14]) available so that only drugs with acceptable effects on the cardiovascular system get into the market [2]. For example, the guideline ICH E14 specifies that thorough QT (TQT) studies have to be performed in humans prior to market authorization, in order to assess the cardiovascular safety in man.…”
Section: Introductionmentioning
confidence: 99%
“…1,5 hERG is mainly involved in repolarization current and its inhibition by drugs or compounds serves as a surrogate for QT (the time between the start of the Q wave and the end of the T wave) prolongation, which itself is a marker for Torsades de Pointes arrhythmia. 6 Most drugs withdrawn from the market appear to inhibit hERG channel activity by in vitro assays. 1,5 In addition to testing for hERG, lead compounds and drug candidates are also subjected to assays, which screen for direct damage to cardiomyocytes at the cellular or organellar level, such as mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…A number of drugs have had to undergo labelling revision or market withdrawal owing to postmarketing reports of sudden cardiac death linked to the development of torsades de pointes (TdP) [4][5][6][7][8][9][10]. It has been demonstrated that an excessive lengthening of cardiac repolarization (measured by QT interval prolongation) may induce these life-threatening ventricular tachyarrhythmias [11].…”
Section: Introductionmentioning
confidence: 99%